Vitamin D therapy's preventive effect in type 2 diabetes mellitus (Journal of the College of Basic Education, 2024)
Diabetes type II (DM II) is becoming more common, and it is highly harmful to several bodily systems. It's critical to keep DM II under control in order to avoid consequences like diabetic nephropathy, peripheral neuropathy, and damage to the retina. The fact that vitamin D lowers hemoglobin A1c (HbA1c) levels is just one of its many benefits. It boosts insulin's sensitivity and secretion. To find pertinent data, we thoroughly searched PubMed, a Medline, PMC, and Google Scholar. Following the application process of the inclusion and exclusion criteria, the studies' quality was assessed using the Cochrane bias analysis, the SANRA (Scale for the Testing of Narrative Review Articles) checklist, the AMSTAR (A Measuring Tool to Assess A Systematic Reviews) criteria, and the AMSTAR criteria. Data has been collected from 14 studies, of which 5 case reports, 3 general articles about DM II and vitamin D, 1 review of the literature, and 8 systematic reviews or meta-analyses.Three were narrative reviews and three were randomized controlled studies. The clinical significance of vitamin D treatment in type 2 diabetes is also evaluated in this study from the perspectives of glucose metabolism and adverse effects such retinopathy, neurotoxicity, and proteinuria. In terms of hemoglobin A1c (HbA1c) reduction, the relief of diabetic neuropathy and nephropathy symptoms, and the reduction of oxidative stress brought on by hypoglycemia in the retinal cells, vitamin D improved glucose levels clinically.One of the essential vitamins for diabetics is vitamin D..